Degradabilidad y cinética ruminal in situ de una mezcla de ensilaje de maíz forrajero (Zea mays) y residuos de banano verde (Musa paradisiaca) en diferentes proporciones en una dieta base. - Jiménez Pincay, Kerly Estefanía (2022)
In the different agricultural productions, feeding is managed with supplements such as free grazing. Concentrated feeds provide the necessary nutritional needs during 365 days of the year, and this would not be achieved if feeding depended only on pasture. Therefore, the objective was to determine the in situ degradability and ruminal kinetics of forage corn silage and green banana residue in different proportions in a base diet. The treatments were T1, corn silage 50% RB 0%; T2 corn silage 45% RB 5%; T3 corn silage 40% RB 10%; T4 corn silage 35% RB 15% and T5 corn silage 30% RB 20%. A DBCA was applied with 5 treatments and 4 replications and Tukey was used for the differences of the means. The material to be ensiled was harvested at 90 days of age (vegetative stage V8). Green banana residues, rice dust, soybean paste and mineral salts were used. The anaerobic fermentation process lasted 30 days, the samples were dried in an oven with forced air at 65ºC for 48 hours, and ground in a Thomas Willy mill with a 2 mm sieve. It was dried in an oven at 65 °C for 48 hours. DISMS and DISMO was used nylon bag in four castrated and rumen fistulated cattle. For each run, seven 10 x 21 cm and 53 mm pore size nylon bags with 10 g of ground sample were used at 0, 3, 6, 12, 24, 48 and 72 hours. The in situ digestibility of DM and OM increased with 20% inclusion of this residue with an effective degradation of 57.23 and 57.05% at a passage rate (k 0.02). The in situ rumen degradability parameters of dry and organic matter of forage corn silage with green banana residues, is a viable alternative using 20% of dry and organic matter due to the dynamics of rumen degradation of DM and OM